Experimental Study of Behavior of Reinforced Concrete One-Way Slabs Strengthened and Repaired by Ferrocement at Tension Zone - ., mazan D.Abdullah (Iraqi Journal of Civil Engineering, 2017)
The principal objective of this paper is to investigation the experimental of the flexural behavior of strengthened and repaired reinforced concrete slabs with ferrocement tension zone. The result of tests on 10 simply supported one way slabs were presented, at which include 1control slab, 5strengthened slabs and 4repaired one way slabs. In the strengthened slabs, the cover of the control slab replacing with ferrocement cover, cold joint between ferrocement layer and the slab, connection type between the ferrocement layer and the slab, on the ultimate load, first crack load, the mid span-deflection, crack width and spacing were examined. In the repaired part the slabs were loaded to (55 %) of measured ultimate load of control slab, the effect of the thickness and number of wire mesh layers on crack pattern, mid span deflection and ultimate load was examined. In the repaired part the slabs were loaded to (55 %) of measured ultimate load of control slab, effect of the number of wire mesh layers of ferrocement on the mid span deflection, ultimate load and crack pattern was examined. The experimental results of strengthened and repaired slabs indicate that; the ultimate loads and mid span deflection were more effected by using ferrocement mortar at tension zone. The increase in ultimate load (8.2-18%) for strengthen slab and (9.1-17.3%) for repaired slab respect to the control slab.